New species of the orb-weaving spider genus Chrysometa (Araneae, Tetragnathidae) from oak forests near of the Pico de Orizaba National Park (Veracruz, Mexico) - Salgueiro-Sepúlveda, F. Javier; Álvarez-Padilla, Fernando (Zootaxa, 2018)
Seven new species of the genus Chrysometa Simon are described: C. citlaltepetl n. sp., C. triangulosa n. sp., C. rosarium n. sp., C. atotonilco n. sp., C. xamaticpac n. sp. C. puya n. sp. and C. sagicuta n. sp. Species identities were evaluated and sexes for each species matched with a fragment of the cytochrome c oxidase subunit I. These data were analyzed with maximum likelihood and the resulting cladograms separated all species with high support values (95–100) and an average distance of 0.093 %. The genetic signal also agreed with the diagnostic morphological features used to separate these taxa. The sex matching results discovered that the female of C. chipinque Levi actually belongs to C. puya n. sp.; the correct female of C. chipinque is here described for the first time. A redescription of the male of C. chipinque and the female of C. puya is also provided. All species were collected as part of a faunistic inventory from two oak forests near Pico de Orizaba Volcano National Park. A total of 399 adult specimens, 209 females and 195 males, were sorted and identified. Most individuals were collected from medium height vegetation by beating trays and from high vegetation by direct collecting at night. High resolution images for all species are available at www.unamfcaracnolab.com. Finally, the functional anatomy of the epigynum for the species described here is discussed.